Financial stability and the Fed: Evidence from congressional hearings - Arina Wischnewsky; David-Jan Jansen; Matthias Neuenkirch (Economic Inquiry, 2021)
This article retraces how financial stability considerations interacted with US monetary policy before and during the Great Recession. Using text-mining techniques, this article innovates by constructing indicators for financial stability sentiment expressed during testimonies of five Federal Reserve Chairs. Including these text-based measures adds explanatory power to Taylor-rule models. Negative financial stability sentiment coincided with a more accommodative monetary policy stance than implied by standard Taylor-rule factors, even during the decades before the Great Recession. These findings are consistent with a preference for monetary policy reacting to financial instability rather than acting pre-emptively to a perceived build-up of risks.
Keywords: 330; financial stability; monetary policy; Taylor rule; text mining